Health education on HPV vaccination and cervical cancer prevention: A randomised controlled trial on knowledge, attitudes, beliefs, and behaviours - Ozdemir, Serpil; Caglayan, Rabia (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the effect of a health education programme on changes in human papillomavirus knowledge, attitudes and intention to vaccinate among adolescent girls and their mothers. Method: The randomised controlled trial was conducted at two adolescent outpatient clinics from January to June 2019 after approval from the Medical Specialist Education Board, Ankara, Turkiye, and comprised girls aged 9-18 years and their mothers. The two clinics were randomised using the lottery method into intervention group A and control group B. The subjects in group A received two health education sessions in addition to standard care: the first session in the first week, and the second session in the fifth week after the first. The follow-up period lasted 12 weeks. Those in group B received standard care. Data was collected using the Human Papillomavirus Knowledge Scale and the Health Belief Model Scale. Data was analysed using SPSS 23. Results: Of the 216 subjects, 108(50%) each were in groups A and B; 54(50%) mothers and as many daughters. There were significant post-intervention differences between the groups (p<0.05). Among group A mothers, the intention to vaccinate their daughters was higher compared to those in group B (p=0.001). Conclusion: Health education regarding human papillomavirus infection and cervical cancer prevention was found to be effective in increasing knowledge and promoting positive health beliefs, attitudes and behaviours. RCT registration: The study was registered at ClinicalTrials.gov (Trial #: NCT04113902 Date of Approval: April 15, 2019). Link: https://www.clinicaltrials.gov/study/NCT04113902 Key Words: Adolescent health, Uterine cervical neoplasms, Health education, Papillomavirus vaccines.